A high‐sensitivity refractometer based on etched thin‐core fiber modal interferometer. Issue 1 (January 2017) - Jiang, Meng; Wang, Ze‐Ming; Zhao, Zhong‐Ze; Li, Kun; Zhang, Yixin
ABSTRACT: We present a high‐sensitivity refractive‐index sensor based on etched thin‐core fiber (TCF) modal interferometer. The sensor structure is formed by splicing a TCF between two single‐mode fibers. To enhance the sensitivity, the thickness of the cladding of sensing region is reduced by hydrofluoric etching. The sensors with different diameters are investigated, and the maximum sensitivity of this new structure is 512nm/R.I.U with fiber diameters of 60 um, which is 4 times higher than that of the basic structure without etching. This structure shows the merits of high sensitivity, low cost, easy control, simplicity of fabrication, and high repeatability. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:53–56, 2017